Fé na vida, fé no homem, fé no que virá: um estudo sobre os sentidos da prática coral em uma unidade prisional - Ricardo Luiz Dias (2019)
In this work, we seek to interpret the meanings and senses attributed by the arrested participants of the Choir of the Associação de Proteção e Assistência aos Condenados (APAC) of Santa Luzia at the time they were singing and performing. For this search, seven arrested singers, who are in the process of resocialization in the institution, were interviewed. Data were collected through semi-structured interviews and analyzed following the principles of phenomenological analysis. Nine categories of meaning emerged which were: 1) singing favoring socialization and sociability; 2) music as leisure and way out of APAC; 3) music and well-being; 4) emotion in singing; 5) musical development: I am not a singer; 6) singing as teamwork; 7) the stigma of being arrested; 8) feeling the absence of the conductor, and 9) the institution. These categories are presented using excerpts from the interviews and discussed in light of Merriam's (1964) assumptions, about the use and social functions of music and Sloboda (2010), about music and emotion, and DeNora (2008), about the use of music in daily life. The results show that the activity was well received by the arrested people, helping them in their resocialization and sociability process, also allowing moments of leisure, assimilation of social rules, musical knowledge and mood regulation. It is also discussed about the use in music in daily life of APAC and how it impacts on the subjectivities of the entervieweds.